The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1191/1078155205jp163cr
|View full text |Cite
|
Sign up to set email alerts
|

Actinic keratosis and capecitabine therapy

Abstract: Topical application of 5-fluorouracil (5-FU) is one of the most effective clinical strategies available to treat actinic keratosis (AK). During treatment, an apparent toxic skin reaction occurs before dermal quiescence ensues. We report a case of a typical flare of AK in a woman treated with capecitabine for advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…Seventy percent of patients reported grade 3 and 4 adverse events; most commonly, fatigue, gout, palmar–plantar erythrodysesthesia, gastrointestinal distress, and reduced kidney function (Table ) . The data presented in this case study as well as those found in previous case reports support the use of capecitabine for the chemoprevention of SCC in solid organ transplant recipients on prolonged immunosuppressive therapy …”
Section: Capecitabinesupporting
confidence: 77%
See 1 more Smart Citation
“…Seventy percent of patients reported grade 3 and 4 adverse events; most commonly, fatigue, gout, palmar–plantar erythrodysesthesia, gastrointestinal distress, and reduced kidney function (Table ) . The data presented in this case study as well as those found in previous case reports support the use of capecitabine for the chemoprevention of SCC in solid organ transplant recipients on prolonged immunosuppressive therapy …”
Section: Capecitabinesupporting
confidence: 77%
“…Previous studies examining the effect of capecitabine on these tumors subsequently discovered that patients who have concurrent actinic keratosis seemed to have some treatment benefit and lesion resolution . Previous case reports on three solid organ transplant recipients and non‐transplant recipients with large NMSC tumor burden showed that low‐dose capecitabine resulted in fewer NMSCs with relatively mild adverse effects . The author of that report published an additional case study on 10 solid organ transplant recipients.…”
Section: Capecitabinementioning
confidence: 99%
“…Other conventional chemotherapeutic agents which have been associated with the inflammation of actinic keratosis include docetaxel, doxorubicin, capecitabine, pentostatin, sorafenib and the combination of dactinomycin, vincristine, dacarbazine and doxorubicin, cytarabine and 6-thioguanine (8,12,23,24). The mechanism by which these agents lead to this effect is unknown, although abnormal DNA synthesis and a form of radiation recall have been postulated (12).…”
Section: Actinic Keratoses and Squamous Cell Carcinomasmentioning
confidence: 99%
“…The data presented in the previous case reports support the use of capecitabine for the chemoprevention of SCC in solid organ transplant recipients on prolonged immunosuppressive therapy [75,76,77]. …”
Section: Classical Therapy Of Nmscsmentioning
confidence: 97%